Stimuli-responsive theranostic system: A promising approach for augmented multimodal imaging and efficient drug release - Demiral, Ayşegül; Goralı, S. İrem; Yılmaz, Hülya; Verimli, Nihan; Çulha, Mustafa; Erdem, Sultan Sibel (Elsevier B.V., 2022)
Destruction of drug resistant and invisible micro-tumors requires innovative screening and treatment modalities. Theranostic nanosystems offering multimodal imaging and therapy are attractive platforms with potential to make micro-tumors visible to clinicians. Gold nanoparticles (AuNPs) are intrinsic theranostic agents and act as fluorescence quenchers. They can be easily transformed to multimodal imaging and combination therapy agents by combining them with various adjuvant therapies such as photodynamic therapy. In this study, we developed a highly specific, hybrid theranostic agent that is only activated when it meets with its stimuli at the site of interest. Surface-coated AuNPs were modified with Cathepsin B cleavable peptide (stimuli responsive linker) and Verteporfin (photosensitizer and fluorescence imaging agent). Unless the theranostic system meets with the internal stimuli in tumor cells, fluorescence is quenched due to AuNP-Verteporfin and Verteporfin-Verteporfin interactions. Following cellular internalization of the theranostic agent, fluorescence is gained by Cathepsin B cleavage and phototoxicity is initiated by light. The system was efficiently internalized by SKOV-3 cells and demonstrated high specificity towards its stimuli. In comparison to Verteporfin, ?14-fold fluorescence increase, 81% fluorescence recovery and comparable toxicity were achieved. The system is a promising candidate for multimodal imaging and dual treatment to destroy the micro-tumors.
Keywords: Cathepsin B; Fluorescence Imaging; Fluorescence Quenching; Gold Nanoparticle; Hybrid Theranostic Agent; Multimodal Imaging; Near-IR Fluorescent Dye; Photodynamic Therapy; Verteporfin